Use of Biosensors within the Oral Environment for Systemic Health Monitoring-A Systematic Review - Natalie Archer; Sa'ada Ladan; Henry T. Lancashire; Haralampos Petridis (MDPI AG, 2024)
Scientific advances in biosensor technology are leading to the potential of wearable biosensors for salivary biomarker detection. This review aims to identify the current status of intraoral biosensor technology that can be used to monitor systemic diseases. A total of 11 studies were identified for inclusion, which included nine different devices, including modified mouthguards, retainers, toothbrushes, and dental floss. Out of the 11 studies, 8 studied continuous biomarker monitoring, and the remaining 3 were point-of-care applications. A total of seven biomarkers were studied, six of which investigated the intraoral detection of salivary glucose levels using glucose oxidase enzyme. All the sensors demonstrated excellent sensitivity (minimum R = 0.9928) and selectivity. The study designs were proof of concept, with five studies including in vivo components. We concluded that while there are established links between salivary biomarkers and systemic health, there is a lack of mature intraoral biosensor research. Refinement of biosensor design and data analysis is required to improve patient acceptability by promoting more discrete, real-time, low-cost, and wireless devices. Further research that utilises the biosensor technology in large controlled clinical trials will be required to confirm clinical applicability before intraoral biosensor technology can be integrated into routine health monitoring.